Daytime sleepiness and academic performance of medical students in a Colombian public university - Ulloque-Caamaño Liezel; Monterrosa-Castro Álvaro; Carriazo-Julio Sol (Revista Ciencias Biomédicas, 2013)
Introduction: Sleep is an important physiological function for the adequate physical,psychological, cognitive and intellectual performance. Excessive daytime sleepinessclassified as moderate or severe is a sleep disorder and its presence in medical studentscould affect in the academic performance.Objective: Establish the prevalence of normal and pathological daytime sleepiness inmedical students.Methods: Prospective and cross-sectional study. Medical students of Medicine of theUniversidad de Cartagena, Colombia in the second academic period of 2011 wereincluded. A survey for the compilation of socio-demographic and academic data andthe Epworth Scale for the assessment of daytime sleepiness were applied. The higherthe score indicates higher daytime sleepiness of the respondent. The participation wasvoluntary and anonymous. A stratified sample by gender and semester was chosen. Dataanalysis was performed using the EPI-INFO statistical program (Version 3.5.1). A p value< 0.05 was considered as statistically significant.Results: 210 medical students filled completely the surveys. The mean age was 19.7±2.0years. 51.0% [CI 95%: 44.0-57.9%] were women and 49.0% [CI95%: 42.1-56.0%]were men. 69% [CI95%: 62.3-75.2%] came from Cartagena and the remaining 31%[CI95%: 24.8-37.7%] came from different provinces. 53.8% [CI95%: 49.8%-60.7%]had sexually active life. The academic mean of all population of students was 3.8±0.28.31.4% [CI95%: 25.2%-38.2%] had high grades, 50.5% [CI95%: 43.5%-57.4%] hadaverage grades and 18.1% [CI95%: 13.1%-24.0%] had regular grades. 19.0% [IC95%:14.0%-25.0%] did not have abnormal daytime sleepiness, 21.4% [CI95%: 16.1%-27.0%] had mild daytime sleepiness, 49.0% [CI95%: 42.1%-56.0%] moderate daytimesleepiness and 10.5% [CI95%: 6.7%-15.4%] had severe daytime sleepiness. 60% ofthe students had pathological daytime sleepiness. The average score of Epworth scale inthe population was 10.6±3.7. Significant difference of diurnal somnolence according tothe nutritional status was observed. The average score of the scale in students with lowweight was 9.1±3.1, normal weight 10.6±3.7, overweight 11.5±3.9 and obesity 5.5±2.1(p=0.03). Also a significant difference according to the sexual activity was observed,11.3±3.9 in students with sexual activity and 9.7±3.3 in those without it (p=0.002).There was not found significant difference in the severity of daytime sleepiness accordingto the range of grades and the academic level.Conclusions: It was observed that six of each ten students presented excessive daytimesleepiness classified as moderate or severe. There were not found differences in theseverity of the diurnal somnolence according to the academic performance. Rev.Cienc.Biomed. 2013;4(1): 31-41.RESUMENIntroducción: el sueño es una función fisiológica importante para el adecuadofuncionamiento físico, sicológico, cognoscitivo e intelectual. La somnolencia diurnaexcesiva de tipo moderada o grave es un disturbio del sueño y su presencia en estudiantesde medicina, pudiese repercutir en el rendimiento académico.Objetivo: establecer la prevalencia de somnolencia diurna normal y patológica enestudiantes de pregrado de medicina.Metodología: estudio de corte transversal prospectivo. Se incluyeron estudiantes depregrado de medicina de la Universidad de Cartagena, Colombia, en el segundo periodoacadémico del año 2011. Se les aplicó un formulario para recolección de informaciónsocio demográfico, académica y la escala de Epworth para evaluar somnolencia diurna. Amayor puntuación mayor somnolencia diurna. La participación fue voluntaria y anónima,escogiéndose una muestra estratificada por sexo y semestre. Los datos fueron analizadoscon Epi-Info 3.5.1. Valor de p<0.05 fue considerado estadísticamente significativo.Resultados: 210 estudiantes de medicina llenaron completamente los formularios. Edadmedia 19.7±2.0. El 51.0% [IC95%: 44.0-57.9%] femenino y 49.0% [IC95%: 42.1-56.0%] masculino. El 69% [IC95%: 62.3-75.2%] procedente de Cartagena y el restante31% [IC95%: 24.8-37.7%] de distintas provincias. El 53.8% [IC95%: 49.8%-60.7%]con vida sexual activa. El promedio académico de toda la población de estudiantes fue3.8±0.28. El 31.4% [IC95%: 25.2%-38.2%] con notas altas, 50.5% [IC95%: 43.5%-57.4%] notas medias y el 18.1% [IC95%: 13.1%-24.0%] notas regulares. No tuvieronsomnolencia diurna anormal el 19.0% [IC95%: 14.0%-25.0%], el 21.4% [IC95%:16.1%-27.0%] presentaron excesiva somnolencia diurna leve, el 49.0% [IC95%: 42.1%-56.0%] moderada y el 10.5% [IC95%: 6.7%-15.4%] grave. El 60% de los estudiantestenía somnolencia diurna patológica. La puntuación promedio de la escala de Epworthen la población fue 10.6±3.7. Se observó diferencia significativa de somnolencia diurnasegún estado nutricional. La puntuación promedio de la escala en estudiantes de bajopeso fue 9.1±3.1, peso normal 10.6±3.7, sobrepeso 11.5±3.9 y obesidad 5.5±2.1(p=0.03). También se observó diferencia significativa según actividad sexual, 11.3±3.9en estudiantes con actividad y 9.7±3.3 en los que no tenían (p=0.002). No se encontródiferencia significativa en la severidad de la somnolencia diurna según el rango de notasni por nivel de formación.Conclusiones: se observó que seis de cada diez estudiantes presentaban somnolencia diurna moderada o grave. No se encontraron diferencias en la severidad de la somnolenciadiurna según el rendimiento académico. Rev.Cienc.Biomed. 2013;4(1): 31-41.